Systematic review on Burnout syndrome in healthcare personnel in Latin America between 2015-2020 - Tapullima Mori, Calixto (2021)
The objective of the study was to evaluate the burnout syndrome in health care personnel in databases containing scientific literature in Latin America between 2015 - 2020, a qualitative, basic approach was used, with a theoretical systematic review design, 43 articles were analyzed ; For the search, 5 databases Scopus, Ebsco, Scielo, Dialnet and Redalyc were reviewed, the keywords were "Burnout syndrome" doctors, "burnout syndrome" "medical personnel," Burnout "doctors and" burnout "health, obtaining as well as Scopus (31), EBSCO (992), Scielo (86) Redalyc (783) and Dialnet (110), thus concluding that most of the articles come from Brazil 14, followed by 8 from Peru, the totality of The studies correspond to an applied type, of which 41 are cross-sectional descriptive, while only 2 are of correlational design, the sample was entirely medical personnel reaching 11693 subjects, finally a high prevalence of burnout syndrome is evidenced as well than in its components, starting from 4.1% to 100% of the medical personnel evaluated.